21.1k views
3 votes
Desperate pls answer!!

Desperate pls answer!!-example-1
User TheNone
by
5.3k points

1 Answer

6 votes

Answer:

Explanation:

a) Since the x's of the original equation are equal to the y's of the inverse equation, and vice versa, you can simply put the x-values of the table for the inverse equation into the y-values of the original equation. The same principle applies to the inverse equation. The table should look like the tables attached.

b) The x's and y's in the points of the inverse are switched. The points will be

(10, 27) --> (27, 10)

(3.5, 14) --> (14, 3.5)

(a, b) --> (b, a)

(x, y) --> (y, x)

Desperate pls answer!!-example-1
User FallAndLearn
by
4.9k points